Collective regulation and the future of work in the digital economy: Insights from comparative employment relations. (June 2022) - Doellgast, Virginia; Wagner, Ines
The impact of technological change on employment, inequality and job quality has attracted considerable analysis from both scholars and practitioners. However, less attention has been paid to how digital technologies are changing contemporary workplaces and how workers are responding to these changes. This article reviews recent research from the multidisciplinary comparative employment relations field, with a focus on institutional resilience or change associated with digitalization; and the strategic responses of unions and other worker representatives to these trends. We find that the insights of economists, sociologists and employment relations scholars are complementary, as each addresses a different dimension of technological change and associated worker outcomes. Comparative employment relations researchers are more likely to influence current debates where they both articulate the unique contribution of their multi-method and comparative research methods and aggregate findings beyond single or paired industry and national case studies.